Diversities of soil weed seed bank and rice yield performance in response to tillage method and weeding regime (Progressive Agriculture, 2016)
Rice field was infested with eight weed species. Among the species found in conventionally tilled plots, the five dominant species ranked in order of importance value were Cynodon dactylon (L.), Paspalum distichum (L.), Cyperus rotundus (L.), Azolla pinnata (L.)  and Cyanotis axillaris (L.) while in stale seedbed the rank was Paspalum distichum (L.), Cynodon dactylon (L.), Cyanotis axillaris (L.), Leersia hexandra (L.) and Cyperus rotundus (L.). There were 15 weed species found in the soil weed seed bank studied at the net house. Among them five species were common of rice field. Ten new species were found in the seed bank. Azolla pinnata (L.), Cyperus difformis (L.) and Paspalum commersonii (L.) of field rice were not found in net house seed bank. In  the field, Cynodon dactylon (L.) was the dominant over Paspalum distichum (L.) but at the net house Paspalum distichum (L.) was dominant over Cynodon dactylon (L.). In seed bank under conventional tillage, 11 species were found consisting of 3559 heads count and in stale seedbed 12 species consisting 3826 heads were counted. Among the identified species, nine were common in both tillage practice. Parapholis strigose (Dumort.) and Phyllanthus niruri (L.) were present in the soil of conventional tillage but not in stale bed while Echinochloa colonum (L.), Fimbristylis miliaceae (L.) and Eragrotis gangetica (Roxb.) were found in stale bed but not in conventional tillage. At the rice field grass weeds were dominant over sedges and broad leaf under the both types of tillage. At the seed bank of net house, grass weeds were dominant over sedges and broadleaf under conventional tillage while under stale seedbed, sedges were dominant over broad leaf and grass. Around 7% higher grain was recorded from stale seedbed compared to conventional tillage which attributed from higher number of effective tillers hill-1, higher number of fertile grains panicle-1, and lower number of sterile grains panicle-1. Weed free condition yield the highest grains followed by the combination of pre and post-emergence herbicides and unweeded control yielded the lowest. Stale seedbed kept weed free yielded the highest followed by stale seedbed sprayed the two herbicides. Conventional tillage remained unweeded yielded the lowest grain.Progressive Agriculture 27 (1): 39-47, 2016